From action intentions to action effects: how does the sense of agency come about? - Chambon, Valérian; Sidarus, Nura; Haggard, Patrick (Frontiers in Human Neuroscience, 2014)
Sense of agency refers to the feeling of controlling an external event through one’s own action. On one influential view, agency depends on how predictable the consequences of one’s action are, getting stronger as the match between predicted and actual effect of an action gets closer. Thus, sense of agency arises when external events that follow our action are consistent with predictions of action effects made by the motor system while we perform or simply intend to perform an action. According to this view, agency is inferred retrospectively, after an action has been performed and its consequences are known. In contrast, little is known about whether and how internal processes involved in the selection of actions may influence subjective sense of control, in advance of the action itself, and irrespective of effect predictability. In this article, we review several classes of behavioural and neuroimaging data suggesting that earlier processes, linked to fluency of action selection, prospectively contribute to sense of agency. These findings have important implications for better understanding human volition and abnormalities of action experience.